2003
DOI: 10.1128/jcm.41.9.4089-4094.2003
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR Assay for Simultaneous Detection of Nine Clinically Relevant Antibiotic Resistance Genes inStaphylococcus aureus

Abstract: In this study we describe a multiplex PCR assay for the detection of nine clinically relevant antibiotic resistance genes of Staphylococcus aureus. Conditions were optimized to amplify fragments of mecA (encoding methicillin resistance), aacA-aphD (aminoglycoside resistance), tetK, tetM (tetracycline resistance), erm(A), erm(C) (macrolide-lincosamide-streptogramin B resistance), vat(A), vat(B), and vat(C) (streptogramin A resistance) simultaneously in one PCR amplification. An additional primer pair for the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
314
5
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(352 citation statements)
references
References 37 publications
9
314
5
6
Order By: Relevance
“…Overall, we found high correlation between these two methods. This correlation has been demonstrated previously in other studies [6,14,15,17].…”
Section: Discussion:-supporting
confidence: 76%
See 2 more Smart Citations
“…Overall, we found high correlation between these two methods. This correlation has been demonstrated previously in other studies [6,14,15,17].…”
Section: Discussion:-supporting
confidence: 76%
“…In recent years, several studies have demonstrated the high capacity of molecular methods such as Pulsed-field gel electrophoresis (PFGE), RT-PCR and PCR-based methods to increase the rapidity and accuracy of resistance testing [1,6,14,15,16,21,22].…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…The total genomic DNA was isolated from staphylococcal strains as described by Hein et al (2005) and further tested by polymerase chain reaction (PCR) method according to Strommenger et al (2003). Primers 16S1 (5-CAGCTCGTGTCGTGAGATGT) and 16S2 (5-AATCATTTGTCCCACCTTCG) rDNA (Generi Biotech s.r.o., Hradec Králové, Czech Republic) typical for the genus Staphylococcus were used for PCR.…”
Section: Genus and Species Identificationmentioning
confidence: 99%
“…To determine whether the isolate would have the characteristic features of CA-MRSA, we conducted genetic studies. The detection of mecA gene and typing of staphylococcal cassette chromosome mec (SCCmec) were performed separately using PCR methods with each specific primer for mecA [4] and for SCCmec [5]. The isolate had mecA gene and SCCmec type IV A (Fig.…”
Section: Case Reportmentioning
confidence: 99%